A systems serology approach to the investigation of infection-induced antibody responses and protection in trachoma - Barton, Amber; Rosenkrands, Ida; Pickering, Harry; Faal, Nkoyo; Harte, Anna; Joof, Hassan; Makalo, Pateh; Ragonnet, Manon; Olsen, Anja Weinreich; Bailey, Robin L.; Mabey, David C. W.; Follmann, Frank; et al. (Frontiers in Immunology, 2023)
Background Ocular infections with Chlamydia trachomatis serovars A–C cause the neglected tropical disease trachoma. As infection does not confer complete immunity, repeated infections are common, leading to long-term sequelae such as scarring and blindness. Here, we apply a systems serology approach to investigate whether systemic antibody features are associated with susceptibility to infection. Methods Sera from children in five trachoma endemic villages in the Gambia were assayed for 23 antibody features: IgG responses towards two C. trachomatis antigens and three serovars [elementary bodies and major outer membrane protein (MOMP), serovars A–C], IgG responses towards five MOMP peptides (serovars A–C), neutralization, and antibody-dependent phagocytosis. Participants were considered resistant if they subsequently developed infection only when over 70% of other children in the same compound were infected. Results The antibody features assayed were not associated with resistance to infection (false discovery rate < 0.05). Anti-MOMP SvA IgG and neutralization titer were higher in susceptible individuals (p < 0.05 before multiple testing adjustment). Classification using partial least squares performed only slightly better than chance in distinguishing between susceptible and resistant participants based on systemic antibody profile (specificity 71%, sensitivity 36%). Conclusions Systemic infection-induced IgG and functional antibody responses do not appear to be protective against subsequent infection. Ocular responses, IgA, avidity, or cell-mediated responses may play a greater role in protective immunity than systemic IgG.